The design thinking method as an example of social innovation in action based on the case study of ProPoLab - Dybał, Mariusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The aim of the paper is to explain and to understand the processes of public services delivery from the perspective of social innovation. Concepts of co-creation and social innovation were elaborated on the basis of one of ProPoLab’s milestones: Design Thinking Workshops. Hence the research object are the residents (mostly seniors) of the district of Popowice, while the quality of life of seniors is its subject. The main research goals were firstly to identify needs of residents in relations to public services, and secondly to design a socially innovative solution that will increase the quality of life of seniors. To achieve these goals, the following research tasks have been set: (a) identifying the needs of seniors, (b) identifying which of those needs are being met locally and which are not, (c) to identify what are the relations between neighbors and the attitude towards cooperation, (d) identifying how the needs of seniors could be met. The research mainly covers the period of 2018–2019. Following research methods have been used: analysis of scientific literature and normative documents, design thinking methodology, comparative analysis and statistical analysis. Utilizing design thinking methodology helped to reveal that the problem of communication between residents can be solved by creating a small, accessibly located community/activity center in their housing estate. This place should meet the needs of activity and self-fulfillment, exchange of information and intergenerational exchange. Time availability is very important, and the space intended for seniors should function in an hourly timeframe similar to daycare centers. Residents should be included in drafting a program to better identify and respond to their needs. Seniors would likely be happy to provide volunteer work in such aplace. The facility should be located in the middle of the housing estate so that all residents have easy access to it, optimally in pleasant natural surroundings (i.e. near vegatation), as well as in close proximity to playgrounds for children.
Keywords: co-creation; design thinking; social innovation